Larch Cellulose Shows Significantly Depleted Hydrogen Isotope Values With Respect to Evergreen Conifers in Contrast to Oxygen and Carbon Isotopes - Arosio, Tito; Ziehmer-Wenz, Malin Michelle; Nicolussi, Kurt; Schlüchter, Christian; Leuenberger, Markus (Frontiers in Earth Science, 2020)
The analysis of the stable isotope of the tree-ring cellulose is an important tool for paleo climatic investigations. Long tree-ring chronologies consist predominantly of oaks and conifers in Europe, including larch trees (Larix decidua) and cembran pines (Pinus cembra) that form very long tree ring chronologies in the Alps and grow at the treeline, where tree growth is mainly determined by temperature variations. We analyzed δ13C, δ18O and δ2H isotopes in the cellulose extracted from tree-rings of wood samples collected at high altitude in the Swiss and Tyrol Alps, covering the whole Holocene period. We found that larch cellulose was remarkably more depleted in deuterium than that of cembran pine, with mean δ2H values of -113.4±9.7‰ for larch and of -65.4±11.3‰ for cembran pine. To verify if these depleted values were specific to larch or a property of the deciduous conifers, we extended the analysis to samples from various living conifer species collected at the Bern Botanical Garden. The results showed that not only the larch, but also all the samples of the deciduous larch family had a cellulose composition that was highly depleted in δ2H with regard to the other evergreen conifers including cembran pine, a difference that we attribute to a faster metabolism of the deciduous conifers. The δ18O values were not statistically different among the species, in agreement with the hypothesis that they are primary signals of the source water. While the δ13C values were slightly more depleted for larch than for cembran pine, likely due to metabolic differences of the two species. We conclude that the deciduous larch conifers have specific metabolic hydrogen fractionations and that the larch unique signature of δ2H is useful to recognize it from other conifers in subfossil wood samples collected for paleoclimatic studies. For climate information the absolute δ2H values of larch should be considered carefully and separate from other species.